Treatment of bilateral ankylosis of the temporomandibular joint with temporalis superficial fascia interpositional flap - Yusuf, Harmas Yazid; Kasim, Alwin; Karasutisna, Tis (Padjadjaran Journal of Dentistry, 2007)
Ankylosis of the temporomandibular joint (TMJ) involves fusion of the mandibular condyle to the base of the skull. Trauma and infection are the leading causes of ankylosis. A case of true bilateral ankylosis of the temporomandibular joint is presented. A 21-year-old male patient had a multiple bone fractures history at the age of 13 due to a sports injury. A TMJ injury might not be detected at that time resulting in a progressive restriction of his mouth opening. He presented with almost complete lack of mobility of the mandible. Surgical treatment was a resection of the ankylotic bone mass, interposition temporalis superficial fascia flaps, and early mobilization and aggressive physiotherapy. The functional results showed good remarks.